Effectiveness of Electronic Medical Records on Patient Safety - Neva CR Sinaga; Bertha Sumartini (Indonesian Journal of Global Health Research, 2025)
This study evaluates the effectiveness of using Electronic Medical Records (EMR) by nurses in relation to service quality and patient safety. Based on the analysis of 10 journals, the results show that the implementation of EMR significantly increases patient satisfaction, reduces medication errors, and improves nurse work efficiency. The study also identifies challenges such as user resistance and technological infrastructure limitations. Overall, EMR has proven effective in enhancing healthcare service quality and patient safety, although further efforts are needed to address implementation barrier. This literature review research aims to find out how the effectiveness of electronic medical records affects patient safety and satisfaction. There were 10 journals used in the literature review. Journal searches were carried out through 3 databases, namely Google Scholar, ProQuest, Emerald Insight, selecting journals using protocol guidelines (PRISMA) starting from identification, screening, eligibility. Literature analysis shows that there is a relationship between Quality, patient safety (IPSG), efficiency, technology and the level of patient satisfaction.